Acute Villitis and Intravascular Microorganisms in Fetal Vessels: A Case Report and Literature Review of an Unusual Histopathological Finding. (June 2021) - Narice, Brenda F; Trzeszcz, Martyna; Cohen, Marta; Anumba, Dilly O
Optimal management of intrauterine infection to avoid serious adverse perinatal outcomes entails prompt administration of antibiotics and consideration of early delivery of the fetus to remove the focus of infection. We report an unusual case of preterm chorioamnionitis which did not improve with sensitive antibiotics, or delivery of the fetus, and ultimately required an emergency hysterectomy to save the mother's life. Interestingly, subsequent histopathological analysis of the post-hysterectomy specimen did not reveal myometrial necrosis or infectious microorganisms. The placental pathological examination, on the other hand, showed evidence of necrotising chorioamnionitis accompanied by a rarely reported lesion: acute villitis with abundant intravascular Escherichia coli, a finding which is strongly associated with fetal demise and adverse maternal outcomes.